Intuitionistic Logic from a Metainferential Perspective - Álvarez Lisboa, Miguel (Logic and Logical Philosophy, 2025)
This paper introduces a metainferential version of intuitionistic logic. I work on the framework proposed by some logicians of Buenos Aires, who defend that a logic should be defined in terms of inferences and metainferences of growing complexity. Three logical systems are presented and proved to be adequate from an intuitionistic point of view